Mengungkap Jejak Iblis dan Syetan Dalam Alquran - Hasiah Hasiah (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2018)
The devil is the effect to fall human to the earth, with the bad way and has delude Adam as and Hawa in the heaven. The devil leave in heaven too with the angel however because reluctance prostration to Adam as. So he is out from the heaven even though to command to prostration to Adam as. That is come from Allah SWT, however the devil rebellious and think He is better than Adam.